Dividend payouts, internal and other external factors, and its impact on stock price - Tribella Kembaren; Noer Azam Achsani; Tb Nur Ahmad Maulana (University of Merdeka Malang, 2019)
This study focuses on the effect of dividend payouts, internal and external factors on stock prices of corporate banking sub-sector. Based on core capital, banking companies in Indonesia are categorized into 4 BUKU (Commercial Bank Based on Business Activities). The findings of this study show that BUKU 4 (its core capital = IDR. 30 billion) provides annual dividend payouts. Its dividend per share, dividend yield, and dividend payout ratio are higher than BUKU bank group 1, 2, and 3. This study also analyzes the effect of dividend payout, Net Interest Margin (NIM), Non-Performing Loan (NPL), inflation rate, interest rate, and Rupiah exchange rate (REER) on the stock prices of 31 banking companies indexed in IDX from annual data over the period of 2013 to 2017. Dividend payout and NIM have a positive and significant effect on stock prices. Panel data regression analysis found that the interest rate has a negative significant effect on stock prices. Meanwhile, the OLS regression test (dummy variable) found that NPL has a negative significant effect on stock prices.JEL Classification: C33, E44, G21DOI: https://doi.org/10.26905/jkdp.v23i2.2520